Temperature and Stress Effects on the Compressive Creep Behavior of Parallel Strand Bamboo - Yanyan Liu; Yulin Bian; Dong He; Jiao Liu; Aiping Zhou (Advances in Civil Engineering)
Parallel strand bamboo (PSB) is an engineered bamboo product fabricated using crushed bamboo fiber bundles. Recently, this product finds applications in the civil engineering field. It is expected that the use of this composite will continue to grow because of its excellent mechanical performance, relatively low variability in material properties, and shape standardization. Modern bamboo structures made from PSB composites may be subjected to temperature variations during service. So far, however, there has been little discussion about the temperature-dependent creep. In this study, an investigation was carried out on the short-term behavior of the compressive property of PSB. A stress range of 8 to 64 MPa over a temperature range of 25°C to 75°C was considered in the 24-hour creep tests. In addition, Burgers model was adopted to describe the short-term creep behavior of PSB. Temperature and stress effects on the creep compliance of the Burgers model were also discussed.